Proses Penerapan Omnibus Law Klaster Ketenagakerjaan pada PT X - Widagdo, Anggoro David; Ferijani, Agatha (JURNAL ILMIAH EDUNOMIKA, 2024)
PT X is a manufacturing company engaged in the field of packaging and printing for product labels. PT X has implemented almost all of Goverment Regulation number 35 of 2021 which is one of the regulations in the Employment Cluster Omnibus Law. Knowing the application of the Omnibus Law which can cause various problems and how company’s management apply these regulations within the company is important to know and worthy of research. The implementation of the FGD is useful for the HRD department in evaluating the implementation of the Employment Cluster of Omnibus Law. As a result of the FGD, several employees still do not understand this latest regulation. Some employees who think they are against it do not know the positive impact. This is because the issues that arise are only negative things about the Employment Cluster Omnibus Law. Limited knowledge also comes from social media and television which often raise negative issues and have a negative impact on employees. Even though it does not cause a reduction in conduciveness in the work environment, HRD department must always monitor all negative issues circulating in the Company and conduct dialogue with employees who are deemed to be causing provocation. Keywords: Employment cluster omnibus law, workforce management, omnibus law polemic